2022
DOI: 10.1039/d1gc04188f
|View full text |Cite|
|
Sign up to set email alerts
|

Direct carbon capture for the production of high-performance biodegradable plastics by cyanobacterial cell factories

Abstract: Plastic pollution caused by non-biodegradable plastics is one of the most widely discussed and notable challenges of the 21st century. Developing biodegradable plastics, such as polylactic acid (PLA), is broadly...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…With the rapid development of biochemical engineering and genetic engineering technology, the biological capture, transformation and utilization of carbon dioxide have made rapid progress as value-added products 45 . Tan et al 46 directly synthesized a degradable plastic PLA from carbon dioxide for the first time in the world, using a combination strategy of metabolic engineering and high-density culture on a light driven cyanobacteria platform. Carbon fixation can not only slow down the greenhouse effect, but also realize non grain fermentation 47 .…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of biochemical engineering and genetic engineering technology, the biological capture, transformation and utilization of carbon dioxide have made rapid progress as value-added products 45 . Tan et al 46 directly synthesized a degradable plastic PLA from carbon dioxide for the first time in the world, using a combination strategy of metabolic engineering and high-density culture on a light driven cyanobacteria platform. Carbon fixation can not only slow down the greenhouse effect, but also realize non grain fermentation 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Using the evolved propionyl-CoA transferase and PHA synthase, lactic acid in microbial cells is first converted to lactyl-CoA and then polymerized to PLA. 33 , 50 , 51 This pathway can support the direct synthesis of PLA polymers in microbial cells, thereby circumventing the complex and expensive chemical polymerization of lactic acid. However, limited by the substrate specificity of propionyl-CoA transferase and PHA synthase, the yield of PLA per dry cell weight is much lower than that of PHB, which greatly increases production costs.…”
Section: Bio-based Production For Biodegradable Plastics and Their Mo...mentioning
confidence: 99%
“…However, the manufacturing of PLAS needs sugar-based feedstocks (e.g., corn starch), which potentially causes competition with food. 10,11 Starch-based straws are also an option for biodegradable straws 12,13 but still face similar dilemmas as PLAS. In addition, Liu et al reported a method to prepare seaweed-based straws as alternatives to plastic straws.…”
Section: Introductionmentioning
confidence: 99%